Added Value of sequentially performed gadoxetic acid‐enhanced liver MRI for the diagnosis of small (10–19 mm) or atypical hepatic observations at contrast‐enhanced CT: A prospective comparison. Issue 2 (13th August 2018) - Yoon, Jeong Hee; Lee, Jeong Min; Lee, Yoon Jin; Lee, Kyung Bun; Han, Joon Koo
Abstract : Background: Small hepatocellular carcinomas (HCCs) often show atypical features at cross‐sectional imaging, yet there is no preferred recommendation for the diagnosis or characterization of small observations (10–19 mm) at present. Purpose: To determine the added value of sequentially performed gadoxetic acid‐enhanced liver MRI for contrast‐enhanced computed tomography (CECT)‐detected small (10–19 mm) or atypical hepatic observations ≥20 mm in the diagnosis of HCC. Study Type: Prospective, cross‐sectional, intraindividual comparison. Population: In all, 110 patients at high risk of developing HCC. Field Strength/Sequence: 1.5T and 3T/T1 ‐weighted imaging. Assessment: Hepatic observations were classified into HCCs or benign non‐HCCs based on imaging features of arterial phase hyperenhancement (APHE) and portal or delayed washout at CT or APHE and portal washout at MRI. Final diagnoses were established using a composite algorithm and diagnostic performances of MRI and CT were compared in all observations. In addition, in a subgroup of histologically confirmed observations and stable benign observations during follow‐up ( n = 94), sensitivity and specificity of MRI were compared between the aforementioned criteria and LR‐5 of Liver Imaging Reporting and Data System v2014. Statistical Test: χ 2 test. Results: MRI provided higher sensitivity than CT (62.2% vs. 27.0%, P = 0.0001) while maintaining specificity (97.2%, each) at the per‐patient level. Among 124 observations, 10–19 mm in size, MRI showed significantly higher sensitivity in diagnosing HCCs (62.5%, 50/80) than CT (25%, 20/80, P < 0.0001) with comparable specificity (97.7% [43/44], each). However, seven atypical observations (≥20 mm) at CT remained atypical at MRI. In the subgroup analysis, the diagnostic criteria of APHE and portal washout showed a significantly higher sensitivity (44.2%, 19/43) than LR‐5 (23.2%, 10/43, P = 0.004), without compromising specificity (97.7% vs. 95.5%). Data Conclusion: Sequentially performed gadoxetic acid‐enhanced MRI provided added value to CECT for the diagnosis of HCCs in small observations by improving sensitivity while maintaining specificity. Level of Evidence: 2 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2019;49:574–587.